2021
DOI: 10.3390/en14123472
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Fuel Consumption and Exhaust Gas Composition of a Diesel Engine Powered by Biodiesel from Waste of Animal Origin

Abstract: The use of biofuel is one method for limiting the harmful impact of diesel engines on the environment. It is also a way of gradually becoming less dependent on the depleting petroleum resources. New resources for producing biodiesel are currently being sought. The authors produced esters from animal fat waste, obtaining a fuel that can power diesel engines and identifying a way to utilise unnecessary waste. The animal fat methyl ester (AME) was produced using a reactor constructed for non-industrial ester prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…During the emissions tests described in this study a fuel mixture consisting of 90% by volume of conventional diesel fuel and 10% by volume of triethylene glycol dimethyl ether (also called triglyme, abbreviation TEGDME) was used. As already mentioned, the authors used this glycol ether in their earlier research on the influence of oxygenated fuels on the exhaust emissions from diesel passenger cars and TEGDME turned out to be one of the most effective oxygenated compounds in reducing exhaust emissions [30]. Detailed results of the research conducted by the authors on the influence of TEGDME on exhaust emissions from a diesel passenger car can be found in [27].…”
Section: Test Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the emissions tests described in this study a fuel mixture consisting of 90% by volume of conventional diesel fuel and 10% by volume of triethylene glycol dimethyl ether (also called triglyme, abbreviation TEGDME) was used. As already mentioned, the authors used this glycol ether in their earlier research on the influence of oxygenated fuels on the exhaust emissions from diesel passenger cars and TEGDME turned out to be one of the most effective oxygenated compounds in reducing exhaust emissions [30]. Detailed results of the research conducted by the authors on the influence of TEGDME on exhaust emissions from a diesel passenger car can be found in [27].…”
Section: Test Fuelsmentioning
confidence: 99%
“…The results obtained in this project show that buses powered by: compressed natural gas, electricity, second-generation biofuels and hybrid configurations combining electricity with hydrogen or a diesel engine are considered as the most promising in terms of technology and environment [27]. There are many studies available in the literature describing the environmental benefits associated with the use of the abovementioned technologies, see, e.g., in [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the submitted works, three papers focus on emission characteristics from different alternatives [2,3,7]. Kuczy ński et al [2] demonstrated that the use of biofuels from waste animal fat allows for a significant reduction in the concentrations of the unburned hydrocarbons (UHC) and particulate matter (PM) when compared to diesel fuel operation.…”
Section: Contributions In This Issuementioning
confidence: 99%
“…Note that the addition of HVO to FAME allows viscosity to be kept at bay while maintaining high cetane number, enabling lower net carbon monoxide (CO) and UHC emissions in a diesel engine. Elevated Nitrogen Oxide emissions remain an issue for oxygenated biofuels [2,3]. Finally, Kryshtopa et al [7] demonstrates that the use of methanol conversion products might be an economically feasible solution to the issue.…”
Section: Contributions In This Issuementioning
confidence: 99%
See 1 more Smart Citation